The Effectiveness of Learning Skill Writing of News Texts with Student Team Achievement Divisions Model and Direct Instruction Based on Language Attitude of Students of Junior High School (Universitas Negeri Semarang, 2018)
Learning in the classroom often makes students have difficulties in distinguishing the content of news texts with other texts. One of the factors that cause this problem is that students do not fully understand news text writing skills, which include assessment of the title, completeness of the elements of news, diction, sentence effectiveness and spelling in the form of news text. The purpose of this study is to examine the effectiveness of learning news text writing skills with STAD and Direct Instruction models based on language attitudes. The design of the study uses a quasi-factorial experiment. The study population is the SMP in Bima Subdistrict using purposive sampling technique. This study used two samples of each class consisting of 32 students namely class VIIIA SMPN 1 Lambu as the experimental class to get treatment using the STAD model and VIIIC class 6 Lambu Junior High School as the control class to get treatment using the Direct Instruction model. Data collection techniques are test and non-test. Data analysis techniques to determine the effectiveness of STAD models using t-test and Anava to determine differences in STAD models and Direct Instruction. The results of the writing skills of the news text STAD model with the average value of the experimental group pre-test 67.59 and the post-test results of 77.78 there were significant differences in the improvement of learning outcomes by 10.19, proved the value of tvalue = 8.459. After using the Direct Instruction model effective in learning news text writing skills from the average pre-test control class of 67.50 and the post-test results to equal to 76.50, there was a significant change of 9, proved tvalue = 13.889. The skill to write news texts on the positive-speaking attitude of students who are treated with the STAD model is better than the writing skills of news texts for students whose positive speaking attitude is treated with the Direct Instruction model.